2018
DOI: 10.1016/j.jimonfin.2018.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and factors of inflation convergence in the European union

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 47 publications
1
7
0
2
Order By: Relevance
“…Potential reasons for the difference between the latter studies and the current one include conducting a time‐varying investigation at the sector level in this paper. Due to these technical reasons, this paper also deviates from studies such as that by Brož and Kočenda (2018), because the convergence process within Europe has been disrupted in certain sectors and countries over time, especially during the 2008 financial crisis.…”
Section: Discussion Of Results and Policy Implicationsmentioning
confidence: 69%
See 1 more Smart Citation
“…Potential reasons for the difference between the latter studies and the current one include conducting a time‐varying investigation at the sector level in this paper. Due to these technical reasons, this paper also deviates from studies such as that by Brož and Kočenda (2018), because the convergence process within Europe has been disrupted in certain sectors and countries over time, especially during the 2008 financial crisis.…”
Section: Discussion Of Results and Policy Implicationsmentioning
confidence: 69%
“…Lopez and Papell (2012) have shown that for EA countries, inflation convergence began shortly after the implementation of the Maastricht treaty, although it has been steadier since the introduction of the euro. Brož and Kočenda (2018) have shown evidence that inflation convergence among EU countries has become more widespread since the global financial crisis of 2008.…”
mentioning
confidence: 99%
“…The international low inflation environment Core CPI inflation in advanced economies Core CPI inflation in emerging market economies The low-inflation phenomenon is also closely intertwined with the ongoing process of integration and convergence in the euro area (López and Papell, 2012;Brož and Kočenda, 2018). In the past two decades, some alignment in cross-country price levels and inflation rates has taken place.…”
Section: Chart 14mentioning
confidence: 99%
“…(2012, Karanasos vd. (2016) ve Brož, ve Kočenda (2018) AB üyeleri arasında enflasyon yakınsamasının varlığını ampirik çalışmalarla araştırmışlar ve genellikle yakınsamanın varlığına dair kanıtlara ulaşmışlardır. Kocenda ve Papell (1997), sanayileşmiş 18 Avrupa ülkesi için yaptığı çalışmada döviz kuru mekanizmasının (ERM) yakınsamayı artırdığını tespit etmiştir.…”
Section: Literatürunclassified
“…Karanasos (2016), EMU üyesi 12 ülke için yaptığı çalışmada ortak para birimine geçişin yakınsamayı etkilemediğini, Euro öncesi ve sonrası dönemde hem mutlak hem de nispi yakınsamanın varlığını tespit etmiştir. Brož, ve Kočenda, (2018) Carcel vd. (2015) ise, EAC ülkelerindeki enflasyon serileri arasındaki eşbütünleşme derecesinin bir veya birden büyük olduğunu tespit etmişler ve bu nedenle uzun vadede şokların etkisinin kalıcı olacağını iddia etmişlerdir.…”
Section: Literatürunclassified